Dynamics of Antarctic and Greenland ice sheets using the borehole, radio sounding and space observations - A. N. Markov; D. Dahl-Jensen; V. M. Kotlyakov; V. N. Golubev; M. G. Leonov; V. V. Lukin (Лëд и снег)
Based on data of measurements in deep ice boreholes, as well as of radar and space geodetic observations in Antarctica and Greenland, a number of new features of the ice mass transport had been revealed. Note that these features do not correspond to the traditional but still hypothetical notions (ideas) of the monotonous and uniform spatial changes in the ice sheet dynamics. Using results of the long-term monitoring of the borehole coordinate axes at the Vostok station (down to 1920 m), east profile Vostok – Vostok 1 – Pionerskaya – Mirny (1409 km, down to the depth of 450 m), and analysis of radar sections, Russian specialists revealed the following: a) the Antarctic ice sheet has stratified changes in speed and a fan-like change in the flow direction along the depth; b) plastic firn layer has individual parameters of dynamics and actually flows down from more monolithic body of the ice sheet (the flow directions differ by 30–80°); c) in some places inside the sheet, the underlying ice masses flow faster than the upper ones. Researchers from the United States and Denmark registered on the radar sections of the lowest third of the ice domes in the central regions of the Antarctica (AGAP) and Greenland (NEEM) some folded structures, which were not typical of ice sheets (vertical amplitude of the folds is about 400 m, inclination of the wings is about 45 degrees or more). The tectonic analysis we have performed allows making a conclusion that a genesis of these ice structures is identical to the diapir folds and to diapirs which are formed at a displacement of lower plastic ice masses by the upper monolithic ones, or to echelon folds of crumpling of lower ice layers at their faster flow along original bed as compared with the overlying ice mass. This makes possible to suggest that a turbulent ice flow can occur in the spacious near-bottom and the most plastic area, and a model of the ice sheet dynamics is considered as extruding of underlying masses by the overlying ones. Specialists of the United States analyzed results of the radar interferometry obtained from satellites of Canada, the US, Europe, and Japan (RADARSAT-1, 2; Envisat ASAR; ERS-1/2; ALOS PALSAR) and determined a velocity of the flow of the day surface of the Antarctic ice sheet. They constructed a map of the 3D-structure of the ice flows and had revealed that the dominating ice diffluence from the central area down to the coastal zone is in a complicated way composed by many local streams. We conducted the morphological analysis and made the conclusion that these flows interact to one another under conditions of the strong differentiation of a surface inclination of the ice flow moving down along the mountain relief of original bedrock, and this process is similar to a merging of glaciers with individual characteristics due to different ice-catchments.